Ceropegia juncea Roxb.: A Review - M., Bhuvaneswari; C., Chitra Vadivu (INTI International University, 2022)
Nature has abundant source of herbs. Each herb have certain phyto-constituents, that isolated substances are utilized as drug. Through this review distribution, morphology, phytochemistry and pharmacological Ceropegia juncea Roxb. were analysed. The steroids, terpenoids, anthocyanins, anthracene glycosides, coumarins, flavonoids, fatty acids, phenolic compounds, alkaloids, carotenoids, tannins, saponins, and carbohydrates, lipids, sugars, potassium, lupeol and stigmasterol are found in preliminary phytochemical analysis. FTIR results have shown the functional groups of alcohol, aldehyde, alkyne, alkene and amines, except ester. The proven results of HPLC & HPTLC showed the presence of cerapegin. Cerapegin is reported to hypotensive, hepatoprotective, antiulcer, antipyretic. Also, the coumarin present in Ceropegia juncea Roxb is found to have anti – coagulant, anti- oxidant, anti – allergic, anti- thrombotic, anti – inflammatory, anti – proliferative, anti-viral, anti- carcinogenic, analgesic activities, cytoprotective and modulatory functions. Coumarin and ceropegin are mostly used to prepare soma drink and also there were 29 components isolated from C.juncea Roxb. The antimicrobial studies also notified in this review. This review summarizes the medicinal value of Ceropegia juncea Roxb. in both traditional and ayurvedic system.